2020
DOI: 10.3390/bios10120211
|View full text |Cite
|
Sign up to set email alerts
|

DNA–Gold Nanozyme-Modified Paper Device for Enhanced Colorimetric Detection of Mercury Ions

Abstract: In this work, a paper device consisted of a patterned paper chip, wicking pads, and a base was fabricated. On the paper chip, DNA–gold nanoparticles (DNA–AuNPs) were deposited and Hg2+ ions could be adsorbed by the DNA–AuNPs. The formed DNA–AuNP/Hg2+ nanozyme could catalyze the tetramethylbenzidine (TMB)–H2O2 chromogenic reaction. Due to the wicking pads, a larger volume of Hg2+ sample could be applied to the paper device for Hg2+ detection and therefore the color response could be enhanced. The paper device a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 43 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Peng and coworkers designed a nanozyme-based paper chip for Hg 2+ detection. 40 DNA-gold nanoparticles (DNA-AuNPs) were chosen as the peroxidase mimic. Hg 2+ could be adsorbed on the surface of DNA-AuNPs, and the formed DNA-AuNPs/ Hg 2+ could show enhanced catalytic activity.…”
Section: Ionsmentioning
confidence: 99%
“…Peng and coworkers designed a nanozyme-based paper chip for Hg 2+ detection. 40 DNA-gold nanoparticles (DNA-AuNPs) were chosen as the peroxidase mimic. Hg 2+ could be adsorbed on the surface of DNA-AuNPs, and the formed DNA-AuNPs/ Hg 2+ could show enhanced catalytic activity.…”
Section: Ionsmentioning
confidence: 99%
“…Accordingly, the development of porous materials with a uniform pore size distribution is essential in improving the reproducibility and detection sensitivity of future lab-on-paper devices. Recent studies have reported that glass fiber paper and nitrocellulose membranes have a uniform pore size distribution [5,10,[16][17][18], and therefore offer an improved detection sensitivity and reproducibility. However, the manufacturing process for such materials is complicated and is more expensive than that for regular paper.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, lab-on-paper diagnostic platforms have aroused great interest in recent years. Compared to traditional macroscale systems, microfluidic lab-on-paper devices have many advantages, including ease of manufacture, good portability, low cost, a simple diagnostic procedure, and good disposability [3][4][5][6][7][8][9][10]. As a result, they are expected to find increasing use for POCT applications in coming years based on a variety of samples, including urine.…”
Section: Introductionmentioning
confidence: 99%
“…1 filter paper) loaded with DNA-Au NPs were also developed to fabricate a paper device for colorimetric detection of Hg 2+ . 56 DNA is an important substance that can control the peroxidase-like activity of various nanomaterials. 57 Thus, DNA-Au NPs could combine with Hg 2+ to produce a more stable DNA-Au–Hg alloy for enhancing peroxidase-like activity.…”
Section: Metal-based Nanozymesmentioning
confidence: 99%